(untitled) (Research, Society and Development, 2021)
Objective: The aim of this study was to verify the influence of 6 weeks of whole-body vibration training on the pro- and anti-inflammatory cytokines (IL-2, IL-4, IL-6, IL-10, IFN-ɣ e TNF-α) in young, eutrophic and sedentary women. Methods: Twenty-six participants were randomly divided into two groups: Vibratory Platform Group (GV, n = 13) and Ergometry Group (GE, n = 13). The training program of both groups was of 20 minutes / session, 3 times per week, in non-consecutive days for 6 weeks. The load of the training was adjusted with the adapted Borg scale. GE was submitted to aerobic activity sessions in a cycle ergometer. GV was submitted to vibration platform stimulation sessions. After training program both groups were submitted to 6 weeks of detraining. Results: GV increased levels of IL-4, IL-6, IL-10 and TNF-α after training, and it decreased all of them after detraining phase. GE increased IL2, IL-4, IL-6 and IL-10 only after the detraining period. Conclusion: 6 weeks of whole-body vibration training can promote an increase in pro- and anti-inflammatory cytokines in young, eutrophic and sedentary women, however these effects seem to be transitory as the exercise is discontinued.